2019
DOI: 10.32553/ijmbs.v3i10.583
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Correlation of Intraocular Pressure Measured by Non-Contact, Rebound and Goldmann Applanation Tonometer With Corneal Thickness, True Iop and Corneal Curvature in a Tertiary Hospital.

Abstract: ABSTRACT: AIM-To compare the intraocular pressure (IOP) measured by Non-Contact tonometer (NCT), Rebound tonometer (RBT) and Goldmann Applanation tonometer (GAT) and their correlation with central corneal thickness (CCT), true IOP and corneal curvature. Reliability of each tonometer. METHODS-500 random patients aged 18 years and above were taken up for the study. Patients with anterior and posterior segment pathologies like corneal ulcer, leukoma, staphyloma, corneal lacerations, ectatic corn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 36 publications
(42 reference statements)
0
0
0
Order By: Relevance
“…[ 14 ] found a good agreement. In a study by Das et al ,[ 6 ] NCT values were higher than the RBT values; the difference noted was 0.6 mmHg, which was statistically significant. In our study, RBT values were much closer but lower than the GAT values; the difference noted was 0.45 ± 2.22 mmHg, which was statistically significant but clinically insignificant.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…[ 14 ] found a good agreement. In a study by Das et al ,[ 6 ] NCT values were higher than the RBT values; the difference noted was 0.6 mmHg, which was statistically significant. In our study, RBT values were much closer but lower than the GAT values; the difference noted was 0.45 ± 2.22 mmHg, which was statistically significant but clinically insignificant.…”
Section: Discussionmentioning
confidence: 80%
“…Similar results were found in studies done by Chakrabarty[ 3 ] (difference of 1.24 ± 1.38 mmHg) and Das et al . [ 6 ] (difference of approximately 1 mmHg). A study from Taiwan[ 11 ] also showed similar findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations